Personal thermal management using portable thermoelectrics for potential building energy saving. (15th May 2018) - Zhao, Dongliang; Lu, Xing; Fan, Tianzhu; Wu, Yuen Shing; Lou, Lun; Wang, Qiuwang; Fan, Jintu; Yang, Ronggui
Graphical abstract: Highlights: Personal thermal management can be applied for building energy saving and improving occupant thermal comfort. A thermoelectric unit is proposed for personal thermal management. Relationship established between personal energy requirement and thermoelectric energy supply. Weight minimization of the thermoelectric unit is achieved. Abstract: Heating and cooling of buildings consume approximately 15% of all energy used in the United States. Such a large energy demand is primarily due to heating and cooling of the entire building space to temperature setpoints usually between 21.1 °C (70 °F) and 23.9 °C (75 °F). However, even with such a narrow range of temperature setpoints, more than 20% of the occupants do not feel thermally comfortable due to individual differences (e.g. age, gender, clothing, or physiology). The personal thermal management techniques, which create a local thermal envelope around a human body instead of heating or cooling the entire building space, have the potential to greatly reduce the building energy consumption and to enhance thermal comfort of individuals. In this study, a portable thermoelectric energy conversion unit (TECU) that converts electricity into cooling and heating energy is developed. The TECU supplies cool air (in the cooling mode) or warm air (in the heating mode) to regulate the thermal comfort of a human body. The cool or warm air is supplied through a tree-like rubber tube network that is knitted into a thermoregulatory undergarment. To achieve a cooling/heating target that provides satisfactory thermal comfort, the required cooling/heating power supply from the TECU is determined first while a theoretical model is then developed to guide the design of the TECU. To minimize the TECU weight and make it suitable for portable applications, relationships between weight and thermal resistances of commercial off-the-shelf heat sinks are established first, and a method to find the minimal weight of heat sinks for the TECU is then developed. This methodology is also applicable for other applications where heat sink weight needs to be minimized. The thermal manikin tests demonstrate that 24.6 W of personal cooling power and 18.5 W of personal heating power are achieved by using the TECU.